1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino‐acid‐sequence Determination and Biological Activity of Cytin, a Naturally Occurring Specific Chymotrypsin Inhibitor from the Leech Theromyzon tessulatum

Abstract: We purified a chymotrypsin inhibitor, designated cytin, from the rhynchobdellid leech Theromyzon tessulatum. This 7.4-kDa peptide was purified to apparent homogeneity by gel-permeation and anionexchange chromatographies, followed by reverse-phase HPLC. The structure of cytin was determined by reduction, S-p-pyridilethylation, automated Edman degradation, and electrospray mass spectrometry. Cytin is formed by the association of two protein chains, which are linked by a disulfide bridge. Chain A consists of 43 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…By contrast, sequence comparisons were carried out for theromin with the four different serine protease inhibitors isolated from the leech T. tessulatum: cytin, therin, therostasin, and tessulin (5,29,(41)(42)(43). This revealed that two of the four (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, sequence comparisons were carried out for theromin with the four different serine protease inhibitors isolated from the leech T. tessulatum: cytin, therin, therostasin, and tessulin (5,29,(41)(42)(43). This revealed that two of the four (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of activated cells was determined as described elsewhere (40). Activated cells not only change their conformation in response to a pharmacological stimulus, but also become mobile and capable of phagocytosis and secrete various signaling molecules (40,41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We now report on yet another inhibitor, designated tessulin. We also demonstrate that this molecule modulates [in conjunction with other T. tessulatum serine-protease inhibitors, such as therin [22], cytin [23] and thero- …”
mentioning
confidence: 57%
“…We now report on yet another inhibitor, designated tessulin. We also demonstrate that this molecule modulates [in conjunction with other T. tessulatum serine-protease inhibitors, such as therin [22], cytin [23] and thero-min (thrombin inhibitor isolated from T. tessulatum ; Matias, I., Malecha, J. and Salzet, M., unpublished results)] the activity of human immunocytes, in a higher manner to aprotinin, a serineprotease inhibitor used to diminish the diffuse inflammatory response associated with major surgery [24,25]. Thus, leeches represent a reservoir of serine-protease inhibitors which are so essential for a parasitic life style involving fluid acquisition when clotting processes are present in the host.…”
mentioning
confidence: 59%